Evaluation of marketing strategies in the context of strategic management in the Banking Industry - Faisal Firman; Sumardi Sumardi; Abdullah Sanusi (Enrichment : Journal of Management, 2023)
An effective marketing strategy is essential for banking companies to achieve a competitive advantage and improve their performance in a competitive market. The purpose of this study is to analyze the effect of marketing strategies on the performance of banking companies and evaluate the extent to which these marketing strategies have successfully achieved the company's business objectives. This study uses a quantitative approach by collecting data from banking companies through surveys and statistical analysis. The data collected include variables related to marketing strategy and firm performance, such as competitive analysis, marketing mix, customer behavior, and technology influence. The results showed that competitive analysis has a positive influence on the performance of marketing strategies of banking companies. In addition, the use of an effective marketing mix also contributes significantly to the performance of marketing strategies. In the same context, customer behavior also has an important influence on the performance of marketing strategies of banking companies. Furthermore, the research findings show that technology has a significant role as a moderating factor in the relationship between marketing strategy and performance of banking companies. Based on the research findings, it can be concluded that effective marketing strategies are essential in achieving good performance for banking firms.